Islamic boarding school management in increasing the effectiveness and creativity of learning at the Islamic boarding school of the modern Islamic boarding school - Widodo, Wahyudi (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Islamic boarding schools are recognized as educational institutions that have made a substantial contribution to the progress and growth of education. Another option for resolving today's educational issues is seen to be Islamic residential schools. The challenge facing today's educational system is coming up with complete, effective, and efficient learning activities that may boost students' learning efficacy and creativity. One of the biggest challenges in implementing education is management, particularly in pesantren, which is well-known in the community for having a traditional system that only focuses on religious science. For this reason, researchers are interested in contemporary boarding schools in an attempt to dispel misconceptions about Islamic boarding schools. The research method used is qualitative. Based on the study findings, it can be inferred that the effect of modernity has led to a general transformation of Islamic boarding schools. With that, there are more and more diverse new and more modern learning resources, as well as the higher the dynamics of communication between the Islamic boarding school education system and other support systems. This illustrates that the administration of Islamic boarding schools at Al-Rifa'ie Modern Boarding School has the ability to enhance the efficiency and ingenuity of student education. The contemporary Al-Rifa'ie boarding school is structured methodically, proficiently, and optimally, including several educational activities. The management includes: management management, infrastructure, human resources. Where from these three main things then succeeded in developing extracurricular and also other equipment related to increasing the effectiveness and creativity of student learning so as to make students more advanced and intelligent. The proof of success is the many achievements that have been achieved by students, both in religious competitions and also general competitions related to student creativity.